Battle of the artificial intelligence: a comprehensive comparative analysis of DeepSeek and ChatGPT for urinary incontinence-related questions - Cao, Huawei; Hao, Changzhen; Zhang, Tao; Zheng, Xiang; Gao, Zihao; Wu, Jiyue; Gan, Lijian; Liu, Yu; Zeng, Xiangjun; Wang, Wei (Frontiers in Public Health, 2025)
BackgroundWith the rapid advancement and widespread adoption of artificial intelligence (AI), patients increasingly turn to AI for initial medical guidance. Therefore, a comprehensive evaluation of AI-generated responses is warranted. This study aimed to compare the performance of DeepSeek and ChatGPT in answering urinary incontinence-related questions and to delineate their respective strengths and limitations.MethodsBased on the American Urological Association/Society of Urodynamics, Female Pelvic Medicine & Urogenital Reconstruction (AUA/SUFU) and European Association of Urology (EAU) guidelines, we designed 25 urinary incontinence-related questions. Responses from DeepSeek and ChatGPT-4.0 were evaluated for reliability, quality, and readability. Fleiss' kappa was employed to calculate inter-rater reliability. For clinical case scenarios, we additionally assessed the appropriateness of responses. A comprehensive comparative analysis was performed.ResultsThe modified DISCERN (mDISCERN) scores for DeepSeek and ChatGPT-4.0 were 28.24 ± 0.88 and 28.76 ± 1.56, respectively, showing no practically meaningful difference [P = 0.188, Cohen's d = 0.41 (95% CI: −0.15, 0.97)]. Both AI chatbots rarely provided source references. In terms of quality, DeepSeek achieved a higher mean Global Quality Scale (GQS) score than ChatGPT-4.0 (4.76 ± 0.52 vs. 4.32 ± 0.69, P = 0.001). DeepSeek also demonstrated superior readability, as indicated by a higher Flesch Reading Ease (FRE) score (76.43 ± 10.90 vs. 70.95 ± 11.16, P = 0.039) and a lower Simple Measure of Gobbledygook (SMOG) index (12.26 ± 1.39 vs. 14.21 ± 1.88, P < 0.001), suggesting easier comprehension. Regarding guideline adherence, DeepSeek had 11 (73.33%) fully compliant responses, while ChatGPT-4.0 had 13 (86.67%), with no significant difference [P = 0.651, Cohen's w = 0.083 (95% CI: 0.021, 0.232)].ConclusionDeepSeek and ChatGPT-4.0 might exhibit comparable reliability in answering urinary incontinence-related questions, though both lacked sufficient references. However, DeepSeek outperformed ChatGPT-4.0 in response quality and readability. While both AI chatbots largely adhered to clinical guidelines, occasional deviations were observed. Further refinements are necessary before the widespread clinical implementation of AI chatbots in urology.